Mainstreaming Informal Financial Institutions - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
Informal financial institutions (IFIs), among them the ubiquitous rotating savings and credit associations, are of ancient origin. Owned and self-managed by local people, poor and non-poor, they are self-help organizations which mobilize their own resources, cover their costs and finance their growth from their profits. With the expansion of the money economy, they have spread into new areas and grown in numbers, size and diversity; but ultimately, most have remained restricted in size, outreach and duration. Are they best left alone, or should they be helped to upgrade their operations and integrate into the wider financial market? Under conducive policy conditions, some have spontaneously taken the opportunity of evolving into semiformal or formal microfinance institutions (MFIs). This has usually yielded great benefits in terms of financial deepening, sustainability and outreach. Donors may build on these indigenous foundations and provide support for various options of institutional development, among them: incentives-driven mainstreaming through networking; encouraging the establishment of new IFIs in areas devoid of financial services; linking IFIs/MFIs to banks; strengthening NGOs as promoters of good practices; and, in a nonrepressive policy environment, promoting appropriate legal forms, prudential regulation and delegated supervision.
Keywords: 330